Ahl al-Sunnah wa al-Jamaah: Satu Pengenalan - Mat, Johari (Jurnal Usuluddin, 1997)
This article tries to introduce ahl al-Sunnah Wa al-Jamaah by referring to its defiliation, background and principle.